Characterization of Liver Function, Immune Response And Hepatitis B Virus (Hbv) Genotypes in Pregnant Women With Malaria-Hbv Co-Infection in Northern Ghana - Anabire, N.G. (University of Ghana, 2017)
Background: The overlap of malaria and chronic hepatitis B (CHB) is common in endemic regions, however, the impact of this co-infection on liver function and immune responses is unknown. This study sought to investigate these interactions in pregnant women reporting to antenatal clinic in the Northern Region of Ghana. Methodology: Levels of malaria parasitemia, hepatitis B viremia, liver biochemical parameters and inflammatory cytokines were assayed and compared across four categories of pregnant women: uninfected, infected with Plasmodium falciparum alone (Malaria group), infected with hepatitis B virus (HBV) alone (CHB group) and co-infected with P. falciparum and hepatitis B virus (Malaria+CHB group). Circulating HBV genotypes were determined by nested PCR. Results: the prevalence of HBV genotypes were: 91.6% genotype E, 5.2% mixed genotypes E/A, and 3.2% mixed genotypes E/D. Relative to the CHB group, the Malaria+CHB group had lower viremia levels (P=0.0157). However, levels of malaria parasitemia were similar in women in the Malaria and Malaria+CHB groups (P=0.3038). Furthermore, levels of markers for liver injury/damage, including alanine aminotransferase (P <0.0001), aspartate aminotransferase (P <0.0001) and total bilirubin (P <0.0001) were elevated in women in the Malaria+CHB group relative to those in the other groups. Similarly, proinflammatory cytokines, including tumour necrosis factor alpha (TNF-α) (P <0.0001), interleukin (IL)-1β (P =0.0270), and IL-6 (P =0.0106) were higher in women with Malaria+CHB compared to those in the other categories. For anti-inflammatory cytokines, including IL-10 (P <0.0001) and IL-4 (P =0.0007), the pattern was exactly the opposite of that for the pro-inflammatory cytokines. Conclusions: The study reports HBV genotype E to be dominant among pregnant women in Northern Ghana. Our findings showed that malaria/CHB co-infection in pregnancy appeared to exacerbate the release of biomarkers for liver damage and inflammatory mediators while reducing immune-modulatory mediators. Recommendation: Further longitudinal studies to investigatechanges in the levels of these biomarkers after the malaria infection is cleared will be important to confirm the findings of this study.
Keywords: Characterization of Liver Function; Immune Response And Hepatitis B Virus; Genotypes in Pregnant Women With Malaria; Hbv Co-Infection in Northern Ghana